PAINTING-COLOR ART (American Journal of Pedagogical and Educational Research, 2023)
Painting is an art form that has existed for thousands of years, dating back to ancient cave paintings found in Lasco, France. It has served as a means of expression and communication for people throughout history and across cultures. Rantasvir is a very ancient art. Its foundation begins with images from the rock. Artists of antiquity were able to achieve a great deal of influence in the works of painting, from a great attention to nature to attention, which at the same time was associated with innovations introduced into the technology of painting. The creation of cartoons of different genres in the Middle Ages enriched the history of painting. The creative search of artists creating in the various currents and directions of the next hundred years gave rise to the new currents of painting (from realism to abstractionism), which were greatly multiplied.